Pathways to research leadership for early career researchers in Africa: A potential role for African and Global Funders - Jackson, J.; Neba, A.; Viney, C.; Mtwisha, L.; de-Graft Aikins, A.; Mitchell, A.; Kebirungi, H.; Outtara, K. (South African Journal of Higher Education, 2022)
Early career researchers at African universities face numerous challenges and demands within a context of minimum resources; yet on the other hand, there is significant expectation for doing excellent science that is of high quality with integrity, while aligning science with societal goals. Furthermore, there is also expectation to increase outputs, make the system more inclusive, attract international partners and contribute to the University’s global rankings. The need therefore to build research capacity, expand the number of active researchers and advance the careers of African researchers has never been more critical, particularly if continental and other global priorities are to be achieved. There is consensus that research leadership is essential to building research capacity in African universities. As a result, there have been increasing investments in building research capacity and research leadership, with initiatives ranging from the creation of north-south research partnerships across disciplines and empirical subjects, to training research leaders and university administrators in top ranking universities in Europe and North America, as well as building the capacity of funders and science systems in Africa. This article will examine the competencies required to be a research leader and the programs that are currently available that support capacity building in research leadership. In addition, it will provide perspectives on the role that global and African funders should play to advance the careers of early career researchers to transition into research leaders, foster innovation, build linkages with policy makers and promote scientific leadership in Africa.